RESPON BEBERAPA VARIETASSTANAMANpCABAIRRAWIT (Capsicum frutescens L.)TTERHADAPPKONSENTRASI PUPUK ORGANIK CAIR - Muhammad Imam Mudin Asrofi; Mohamad Ihsan, Tri Pamujiasih (PROSEDING, 2022)
Thissstudy was conducted toddetermine the response of the concentration of liquid organicvfertilizer to theigrowth and yield of several varieties of cayenne (Capsicum frutescens L.). This researchlwas conductedlfrom November 2018 toxFebruary 2019, in KagokanxVillage, Gatak Subdistrict, Sukoharjo Regency at an altitude of 104 mlasl.XThis researchXused aXfactorial method with aXRandomized Completely BlockXDesign (RCBD) patternXconsisting of twoZtreatment factors.ZThe first treatment factor is theXconcentration ofXliquidZorganic fertilizer (C) whichNconsists of 4Clevels (C0 = without (LOF), C1 = 3 cc / l water, C2 = 5 cc / l water, C3 = 7 cc / l water). The second treatment factor, the variety of cayenne varieties (V) consisting of 2 kinds (V1 = cayenne pepper varieties Taring, V2 = cayenne pepper varieties CF 291). Data analysis using variance with the F testxat the level of 5% and 1% andxif the different treatments were significantly continued with the Duncan MultipleXRange Test (DMRT) atqthe level of 5%. Thexresults of thisnstudy indicate that: the treatmentxof the concentrationqof liquid organicmfertilizer has a very significantneffect on plant height, fresh weight and, drybweight of crown and weight of fruit per plot while significantly affecting the number of fruitslper plantzand weightzof fruit per plant. The best concentration of liquid organic fertilizer in treatment reached of 7 cc / l water organox concentration. Kind of variety have a very significantheffect on plant height, fresh weight and dryjweight of crown and weight of fruit per plot, while significantly influencing theinumber of fruitsmper plant and weightzof fruit per plant.tThe interactiondbetween the concentration of liquid organickfertilizer and the variety of cayenne the best result shows that the best result of all parameters is a combination of Taring variety with 7 cc / l water of liquid organic fertilizer treatment, this combination gave the weight of fruit per plot, which was 438,60 g, and made the lowest weight of fruit per plot on the CF 291 variety with no concentration liquid organic fertilizer treatment combination of 153,13 g. Keywords: Varieties, Liquid Organic Fertilizer, Cayanne Pepper